sero-prevalance of Toxoplasma gondii among Diabtic patients in Thi-Qar province/ south Iraq - sadoon, Maha m.; Khalaf, Amal kh. (University of Thi-Qar Journal of Science, 2022)
Toxoplasmosis is one of the most widespread diseases in the world. It is known for being asymptomatic and affects all living organisms, including humans. The disease is caused by the Toxoplasma gondii parasite. Immunocompromised patients such as AIDS and diabetes ,are the most vulnerable group to infection .The main objective of this research is to detect the infection with Toxoplasma gondii among Diabetic patients by serological method (ELISA) in order to measure the level of IgG for 120 of diabetic patients and 60 healthy control .The results were showed that 35% of diabetic patients infected with Toxoplasma gondii compare to control 78.3% .The age of Diabetic patients who are infected with toxoplasmosis was 55-65 and consisted 11.6% rate of infection followed by 8.3% in 45-55 age group ,while the lower rate was 1.1% in age group of 75-85 years. Diabetic female 34.1% was highly infected with toxoplasmosis than male o.8%, and their residency were urban (24.1%).